Antioxidant Activity Test of Pulutan (Urena lobata Linn) Leaf Ethanol Extract from Barru District Using the DPPH Method - Putri, Hartina Febriani (Makassar Natural Product Journal (MNPJ), 2024)
Pulutan (Urena lobata Linn) is one of the many wild plants that can be found in Barru district. Pulutan leaf extract has several properties including being an antioxidant, antibacterial, antifungal, and can inhibit the growth of breast cancer cells. Pulutan leaf extract contains flavonoids, alkaloids, cardiaglycosides, tannins, terpenoids and saponins. This study aims to analyze the antioxidant activity of the ethanol extract of pulutan leaves using the DPPH free radical scavenging method. This type of research is laboratory experimental using the spectrophotometer method based on the calculation of the IC50 value of the extract on DPPH free radical activity.The stages of this research began with the preparation and extraction of samples, preparation of blank solutions and measurement of the maximum wavelength, and ended with testing the antioxidant activity of extracts and quercetin standards. This research obtained yields of percent reduction of 3.241%; the value of the extract regression equation is the value of y = 0.0693x + 30.489 (r = 0.9963); and IC50 value of 281 μg/mL. The results of this study illustrate that the ethanol extract of pulutan leaves has antioxidant activity but is in a weak antioxidant category. Keywords: Pulutan (Urena lobata Linn) leaves; antioxidants; DPPH; Spektrofometer uv-vis